Increased sensitivity of Au-Pd nanolayer on tapered optical fiber sensor for detecting aqueous Ethanol - Muhammad Noor, Ahmad Shukri; Talah, Ali; Rosli, Mohd Anwarul Arif; M. Thirunavakkarasu, Punithavathi; Tamchek, Nizam (SpringerOpen, 2017)
Background: Optical fiber sensors gains popularity as an alternative and a better solution compared to its electronics counterpart. Especially in detecting hazardous materials, optical fiber sensors prove to have many advantages such as miniaturization, remote yet real-time sensing and immune to electromagnetics interference. Methods: In this paper, we used a 40um tapered standard multi-mode fiber coated with gold (Au), palladium (Pd) and mixtures of Au-Pd nano-composites to detect hazardous ethanol in its various concentration in aqueous environment. Interrogation were made possible using UV-VIS light source, and changes in absorbance and intensity were recorded via spectrometer. Results and Conclusion: Ethanol ranging from 20% till 100% were investigated. It was found that the composition of nanomaterial coating on the developed sensors strongly affected the sensing performance. From the experiments carried out, the sensor with a gold palladium nanocomposite layer with a 2: 1 ratio of gold to palladium produced the highest sensitivity, which is 0.74/vol% concentration of Ethanol. The fabricated fiber sensor also exhibits fast response and recovery time of 13 s and 6 s respectively.